Dampak dekadeksi moral pada kecerdasan emosional dalam pembentukan karakter siswa SMA - diana12, zulfa ulya (Maliki Interdisciplinary Journal, 2026)
Moral decadence among high school students is evident in a decline in respect for teachers and parents, increased bullying behavior, cheating habits, and misuse of social media. This condition reflects a weak instillation of moral values ​​and emotional control, which play a crucial role in character formation. This study aims to describe the forms of moral decadence, identify the causal factors, and analyze its impact on students' emotional intelligence. The approach used is descriptive qualitative with a literature review method from various relevant scientific sources. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions using content analysis techniques. The results show that moral decadence is caused by the influence of the family, school, peer group, and globalization environments. The resulting impacts include a decline in students' ability to control emotions, empathy, and decision-making, which has implications for weak character and social behavior. Preventive efforts can be carried out through synergy between families, schools, and communities in strengthening character education and moral guidance for students.